Digital Marketing Workshop for SMEs in Kiaracondong During COVID-19 Pandemic - Siti Rosimah; R. Indriyati Kamil; Dinna Charisma (Journal of Innovation and Community Engagement, 2022)
In the face of the COVID-19 coronavirus pandemic, the role of small and medium enterprises (SMEs) needs to be strengthened. Especially now that small and medium enterprises are no longer seen as an alternative, but as the backbone or foundation of the country's economy. There are three things that must be considered and improved in an effort to strengthen the existence of SMEs, namely finance, improving Human Resources (HR) and innovating marketing models through digital technology. MSMEs in Kiaracondong District which are engaged in culinary and handicrafts are small businesses owned and developed by individuals in the guidance, direction and supervision of the Head of the Economic and Development Section at both the sub-district and village levels. In the time of COVID-19 pandemic, the majority of MSMEs in the Kiaracondong sub-district tend to experience a decrease in sales turnover, this is because the marketing of their products is still done conventionally and only around the neighborhood where they live. Therefore, the Langlangbuana University community service team provides assistance to SMEs to develop their entrepreneurial spirit, through discussion methods and FGDs for product innovation assistance, sales promotion strategies, online marketing strategies and digital literacy. The results of the mentoring activity showed that the SME participants in the Kiaracondong sub-district actively participated in mentoring activities and could understand the strategy for developing product variations and understanding digital literacy in marketing their products through social media such as Whatsapp groups and business WhatsApp, Facebook, and Instagram.